R for programmers : mastering the tools - Zhang, Dan (Online access with DDA: Askews (Maths), 2016)
Examining cases with valuable combinations of interdisciplinary knowledge, theory, and practice, this thorough resource for programmers serves as a reference book on R, introducing more than 30 R packages that are convenient to look up, and will help readers extend their scope of knowledge. --